Problems of correction and reconfiguration of multimedia traffic transmission trakts in wireless networks - Искренко, Ю. Ю. (Problems of Informatization and Control, 2014)
The most rational way in performing a decision of given problem is the use of broadband WIMAX networks. To achieve a maximal efficiency we will consider several methods of WIMAX multiband antennas reconfiguration and arrangement